Prospective Phase II trial of radiation therapy in localised non-gastric marginal zone lymphoma with prospective evaluation of autoimmunity and Helicobacter pylori status: TROG 05.02/ALLG NHL15. (July 2021) - MacManus, Michael P.; Roos, Daniel; O'Brien, Peter; Capp, Anne; Wirth, Andrew; Tsang, Richard; Bressel, Mathias; Lade, Stephen; Seymour, John F.
Abstract: Background: This Phase 2 multicentre trial in localised non-gastric marginal zone lymphoma (MZL) evaluated the effectiveness and safety of radiotherapy and documented markers of autoimmunity and Helicobacter pylori infection. Patients and methods: Eligible patients had Stages I and II or paired-organ, non-gastric MZL. Bone marrow evaluation, autoantibody panel, and H . pylori  evaluation were mandatory. Involved-field or involved-site radiotherapy was delivered to 24–30.6 Gy. Detected H. pylori  infections underwent eradication. Results: Between 2006 and 2014, six centres enrolled 70 patients, and 68 commenced treatment. The median age was 59 (range: 23–84) years, and 31 (46%) were male. Overall, 55 patients had Stage I disease, nine patients had Stage II disease, and four patients had paired organ–confined disease. Involved extranodal sites with three or more cases were orbital (n = 18), conjunctiva (n = 13), lacrimal (n = 8), skin (n = 8), salivary (n = 7), and muscle (n = 4). Eight patients had primary nodal MZL. At the median follow-up of 5 years (range 0.7–9.4), progression-free survival and overall survival were 79% and 95%, respectively. One lymphoma-related death and two in-field failures (after 25 and 30 Gy, respectively) occurred. Distant relapse sites were skin (n = 2), lymph nodes (n = 2), duodenum, stomach, muscle, and conjunctiva (1 each). No paired-organ MZL relapsed. Apart from cataracts (n = 18), only three treatment-related late grade ≥3 adverse events occurred. Autoantibodies or autoimmune events were detected in 26 of 68 patients (38%). H. pylori  infection was detected in 15 of 63 patients (24%) tested. Neither autoimmunity nor H. pylori  was detected in 27 of 68 patients (40%). Conclusions: Radiotherapy was a potentially curative treatment with low toxicity in localised non-gastric MZL. Autoimmunity, H. pylori  infection or both were detected in 60% of patients. Highlights: Largest prospective radiotherapy trial in non-gastric marginal zone lymphoma. Conducted to a high standard by a cooperative oncology group with quality assurance. Unique prospective autoimmunity data in non-gastric marginal zone lymphoma. Prospective evaluation for Helicobacter pylori infection. Trial is among the highest-level evidence currently available in this disease.